Myelopoiesis of the Amphibian Xenopus laevis Is Segregated to the Bone Marrow, Away From Their Hematopoietic Peripheral Liver - Yaparla, Amulya; Reeves, Phillip; Grayfer, Leon (Frontiers in Immunology, 2020)
Across vertebrates, hematopoiesis takes place within designated tissues, wherein committed myeloid progenitors further differentiate towards cells with megakaryocyte/erythroid potential (MEP) or those with granulocyte/macrophage potential (GMP). While the liver periphery (LP) of the Xenopus laevis amphibian functions as a principal site of hematopoiesis and contains MEPs, cells with GMP potential are instead segregated to the bone marrow (BM) of this animal. Presently, using gene expression and western blot analyses of blood cell lineage-specific transcription factors, we confirmed that while the X. laevis LP hosts hematopoietic stem cells and MEPs, their BM contains GMPs. In support of our hypothesis that cells bearing GMP potential originate from the frog LP and migrate through blood circulation to the BM in response to chemical cues, we demonstrated that medium conditioned by the X. laevis BM chemoattracts LP and peripheral blood cells. Compared to LP and using a comprehensive panel of chemokine genes, we showed that the X. laevis BM possessed greater expression of a single chemokine, CXCL12, the recombinant form of which was likewise chemotactic to LP and peripheral blood cells and appeared to be a major chemotactic component within BM-conditioned medium. In confirmation of the hepatic origin of the cells that give rise to these frogs’ GMPs, we also demonstrated that the X. laevis BM supported the growth of their LP-derived cells.